Confocal laser scanning microscopy and area-scale analysis used to quantify enamel surface textural changes from citric acid demineralization and salivary remineralization in vitro. Issue 2 (February 2016) - Austin, R.S.; Giusca, C.L.; Macaulay, G.; Moazzez, R.; Bartlett, D.W.
Highlights: We characterize optical and mechanical properties of enamel surfaces during erosion and remineralization. 3D imaging of enamel surfaces undergoing erosive wear requires instrumentation with lateral resolution significantly less than 5 μm. 3D surface texture parameters are able to successfully characterize textural changes in enamel during erosive demineralization and salivary remineralization. The role of surface texture in remineralization is less clear but suggests that in vivo remineralized lesions remain rougher despite the surface microhardness recovering to baseline levels. Abstract: Objectives: This paper investigates the application of confocal laser scanning microscopy to determine the effect of acid-mediated erosive enamel wear on the micro-texture of polished human enamel in vitro . Methods: Twenty polished enamel samples were prepared and subjected to a citric acid erosion and pooled human saliva remineralization model. Enamel surface microhardness was measured using a Knoop hardness tester, which confirmed that an early enamel erosion lesion was formed which was then subsequently completely remineralized. A confocal laser scanning microscope was used to capture high-resolution images of the enamel surfaces undergoing demineralization and remineralization. Area-scale analysis was used to identify the optimal feature size following which the surface texture was determined using the 3D (areal) texture parameter Sa. Results: The Sa successfully characterized the enamel erosion and remineralization for the polished enamel samples ( P < 0.001). Significance: Areal surface texture characterization of the surface events occurring during enamel demineralization and remineralization requires optical imaging instrumentation with lateral resolution <2.5 μm, applied in combination with appropriate filtering in order to remove unwanted waviness and roughness. These techniques will facilitate the development of novel methods for measuring early enamel erosion lesions in natural enamel surfaces in vivo .